Sustainable Social Entrepreneurs Collaborate – Ashoka A Case Study - Naidu, Sathvika (2006)
Social Entrepreneurs are the answer to solving the world’s complex social problems. They need to become Sustainable if they want to survive and have the desired impact. Because funding from traditional sources is diminishing and there is intense competition for these scarce resources. On the other hand businesses, where there is concentration of wealth, are now being encouraged to engage in a more proactive approach to solving the world’s complex problems. While nonprofit’s are searching for the holy grail of financial sustainability. Ashoka a nonprofit organization, who is a pioneer in this field are presently concentrating on building bridges between social entrepreneurs and businesses to demonstrate how, by collaborating they can construct hybrid social-business ventures: new business models that build wealth, repair the earth, and address major social problems at the bottom of the pyramid. The concept of ‘the opportunity at the bottom of the pyramid’ states that doing business with the world’s 4 billion poorest people represents a multi trillion-dollar market according to management guru CK Prahalad. This research is a case study analysis of Ashoka. The objective of this research is to identify if the key to success that enables a social entrepreneur to become sustainable is ‘the strategy of collaborating using the hybrid value chain and taking advantage of the opportunities at the bottom of the pyramid’. By interviewing seven social entrepreneurs from Ashoka and nine business stakeholders hypothesis are tested. To further validate the findings four sustainable social entrepreneurs’ case studies are analyzed in order to come up with a final central research proposition to answer the central research question presented as: ‘Why are some social entrepreneurs from Ashoka sustainable?’. Is it time to bridge the gap between businesses and nonprofits? They have lived in separate worlds for too long. By collaborating using the hybrid value chain concept can they achieve their aims together by taking advantage of the opportunities at “the bottom of the pyramid”.